Trends and controversies: AI, virtual worlds, and massively multiplayer online games - CHEN, Hsinchun (Institutional Knowledge at Singapore Management University, 2011)
The rich social media data generated in virtual worlds has important implications for business, education, social science, and society at large. Similarly, massively multiplayer online games (MMOGs) have become increasingly popular and have online communities comprising tens of millions of players. They serve as unprecedented tools for theorizing about and empirically modeling the social and behavioral dynamics of individuals, groups, and networks within large communities. Some technologists consider virtual worlds and MMOGs to be likely candidates to become the Web 3.0. AI can play a significant role, from multiagent avatar research and immersive virtual interface design to virtual world and MMOG Web mining and computational social science modeling. This issue includes articles with research examples from distinguished experts in social science and computer science. Each article presents a unique research framework, computational methods, and selected results.